2021
DOI: 10.1002/cncr.33629
|View full text |Cite
|
Sign up to set email alerts
|

Delays in breast cancer care by race and sexual orientation: Results from a national survey with diverse women in the United States

Abstract: BACKGROUND: Despite known differences in breast cancer by both race and sexual orientation, data on the intersectional experiences of Black sexual minority women (BSMW) along the care continuum are scant. This study sought to understand delays in breast cancer care by examining the intersection of race and sexual orientation. METHODS: This online, cross-sectional survey enrolled racially and sexually diverse women aged ≥ 35 years who had been diagnosed with breast cancer within the prior 10 years or had an abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 41 publications
0
16
0
1
Order By: Relevance
“…Comorbidity is typically higher and evident at a younger age in ethnic minority groups as a result of socio‐economic inequality (Ellis et al, 2018 ; Lundqvist et al, 2016 ; Sparano & Brawley, 2021 ), which may impact on medication beliefs and adherence. Stigma, perceived discrimination and lack of social support (Jones et al, 2014 ; Kang et al, 2020 ) might be associated with adherence due to mistrust of healthcare professionals (Fujisawa & Hagiwara, 2015 ) and have been found to be higher in African American women compared to White women (Jones et al, 2014 ; Poteat et al, 2021 ) with perceived empathy from healthcare professionals being lower in women from minority ethnic groups (Moon et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidity is typically higher and evident at a younger age in ethnic minority groups as a result of socio‐economic inequality (Ellis et al, 2018 ; Lundqvist et al, 2016 ; Sparano & Brawley, 2021 ), which may impact on medication beliefs and adherence. Stigma, perceived discrimination and lack of social support (Jones et al, 2014 ; Kang et al, 2020 ) might be associated with adherence due to mistrust of healthcare professionals (Fujisawa & Hagiwara, 2015 ) and have been found to be higher in African American women compared to White women (Jones et al, 2014 ; Poteat et al, 2021 ) with perceived empathy from healthcare professionals being lower in women from minority ethnic groups (Moon et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For an example, an editorial stated that SGD African Americans face multiple healthcare disparities due to the role racism and discrimination has played over decades in policy making and medical practice [5 ▪▪ ]. This notion was confirmed in a recent cross-sectional survey which revealed that 29% of Black sexually diverse (SD) women with breast cancer chose to delay care due to barriers such as past negative healthcare encounters, other priorities or struggles relating to scheduling an appointment [6 ▪ ]. Those Black SD women with breast cancer who engaged in cancer treatment often faced Healthcare Provider (HCP) assumptions, mistreatment and felt misunderstood during their care according to a review on the topic [7].…”
Section: Resultsmentioning
confidence: 99%
“…Unemployment influences behaviours towards cancer care (eg, people may not find time to take up cancer screening; or patients might prioritise work over treatment if absenteeism implies loss of income) 24. Mistrust of healthcare professionals by people from minority ethnic populations and sexual minority groups,25–27 and perceptions and experiences of discrimination and racism28 29 impact uptake of health services.…”
Section: Study Rationalementioning
confidence: 99%